A study the level awareness of saving behavior among students at Politeknik Kota Bharu, Kelantan, Malaysia / Norsyafinaz Abdul Aziz and Farhana Syahira Kamaludin - Abdul Aziz, Norsyafinaz; Kamaludin, Farhana Syahira (2014)
This major purpose of this study is to examine the level awareness of saving behavior among students at Politeknik Kota Bharu, Kelantan that influence by financial socialization, financial literacy and childhood consumer experience. Questionnaires were distributed and self-administrated to 150 respondents at Politeknik Kota Bharu, Kelantan. The objectives of this research is to identify the relationship between financial socialization and saving behavior, the relationship between financial literacy and saving behavior and the relationship between childhood consumer experience and saving behavior among students at Politeknik Kota Bharu. Descriptive analysis, reliability analysis, Pearson Correlation analysis and linear regression analysis were used in this study. The research resulted showed that all independent variables which were financial socialization, financial literacy and childhood consumer experience has significant relationship with saving behavior.